Cooperation in the Workplace - Silvia Castro; Hoa Ho; Maren Alana Mickeler (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2025)
Organizations rely on peer-to-peer knowledge exchange among employees, yet incentivizing cooperative behaviors is a challenge. This study evaluates an intervention designed to encourage peer support in the largest bank in Uganda. Using a cluster randomized controlled trial, we introduced a public recognition incentive-awarding employees identified as the most supportive by their peers and supervisors. The intervention increases employees' willingness to help by 21% in expertise-sharing and 12% in mentoring. The incentive's effectiveness stems from its role in enhancing professional reputation and career prospects. A replication exercise in a second bank confirms the findings and the external validity of the results.
Keywords: M52; D23; J24; M54; C93; D83; 330; workplace cooperation; peer recognition; organizational incentives; knowledge sharing; field experiment; employee motivation; randomized controlled trial (RCT)